Encrypted Email For Local Government Information Security In South Sumatra - Ratu Mutialela Caropeboka; Januar Effendi; Isna Wijayani; Rahma Santhi Zinaida (JINAV: Journal of Information and Visualization, 2022)
This study obtains an overview of the conditions of the encryption email management workflow among local governments in South Sumatra. The workflow for managing email encryption for regular official news has been going very well. Meanwhile, the workflow for managing encryption of emails for confidential news is still experiencing problems, especially for local governments that do not have cipher expert personnel and official cipher equipment from the BSSN. In addition, this study also illustrates that the application of information security theory in the use of encrypted emails for confidential news between local governments in South Sumatra is not optimal. The main obstacle faced is that there are still local governments that do not have cipher expert personnel and official cipher equipment from the BSSN. The quality of the workflow is measured by looking at the fulfillment of the main elements contained in the Standard Operating Procedures (SOP) of the encryption email management workflow. The quality of using email encryption for information security is carried out by analyzing the fulfillment of the elements contained in the information security theory.